HUBUNGAN KOMUNIKASI ANTAR PENJUAL DENGAN PEMBELI IKAN NILA DI PASAR SENTRA ANTASARI BANJARMASIN - Zainal Hakim; Muhammad Yunus Jarmie; Deli Anhar (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2014)
Three objectives to be achieved, the first communication between the members to know the seller.Second to determine the communication between fellow shoppers, and the third to find out the communication between the various sellers with buyers. The experiment was conducted in April, May and June 2013 in the city of Banjarmasin. As a qualitative research, preliminary research was conducted to determine the characteristics of informants in various sellers tilapia and many buyers tilapia.The results showed that the first communication between the members of the seller is seeking the material, which consists of tilapia as a sideline business, a variety of businesses, specifically businesses. The location of the sale transaction market activity in farming locations, sold in the market and sold freely on the agreement. The second communication between fellow shoppers they give each other the location where the sales information tilapia and tilapia freely purchase, subscription, or in the form of foster father. The third communication between sellers with buyers both in the location of tilapia farming and market centers Banjarmasin Antasari conducted through face-to-face, via telephone, internet, messaging via SMS, or via private message. Communication link between sellers with buyers there is a change of pattern-free relationship, increase in subscription relationship. The relationship progresses foster father and began to develop business partner relationships. Keywords: Relationship, Communication, Sellers and Buyers